A Homozygous Deep Intronic Mutation Alters the Splicing of Nebulin Gene in a Patient With Nemaline Myopathy - Laflamme, Nathalie; Lace, Baiba; Thonta Setty, Samarth; Rioux, Nadie; Labrie, Yvan; Droit, Arnaud; Chrestian, Nicolas; Rivest, Serge (Frontiers in Neurology, 2021)
Nemaline myopathy is a rare disorder affecting the muscle sarcomere. Mutations in nebulin gene (NEB) are known to be responsible for about 50% of nemaline myopathy cases. Nebulin is a giant protein which is formed integrally with the sarcomeric thin filament. This complex gene is under extensive alternative splicing giving rise to multiple isoforms. In this study, we report a 6-year-old boy presenting with general muscular weaknesses. Identification of rod-shaped structures in the patient' biopsy raised doubt about the presence of a nemaline myopathy. Next-generation sequencing was used to identify a causative mutation for the patient syndrome. A homozygous deep intronic substitution was found in the intron 144 of the NEB. The variant was predicted by in silico tools to create a new donor splice site. Molecular analysis has shown that the mutation could alter splicing events of the nebulin gene leading to a significant decrease of isoforms level. This change in the expression level of nebulin could give rise to functional consequences in the sarcomere. These results are consistent with the phenotypes observed in the patient. Such a discovery of variants in this gene will allow a better understanding of the involvement of nebulin in neuromuscular diseases and help find new treatments for the nemaline myopathy.